Durability Performance of Concrete Structures Built with Low Carbon Construction Materials. (June 2016) - Pasupathy, Kirubajiny; Berndt, Marita; Sanjayan, Jay; Pathmanathan, Rajeev
Abstract: Here, we demonstrate the feasibility of industrial application of low carbon supplementary cementitious materials (i.e. geopolymer concrete) by investigating the durability performance of eight years aged reinforced geopolymer concrete structure exposed to ambient environment. The corrosion performance of reinforcement bar in concrete and permeability characteristic of cover concrete is investigated by using non-destructive techniques. The results reveal that the reinforcement in geopolymer concrete exhibits higher corrosion risk in atmospheric environment and this attributes to the deterioration of long term durability performance for geopolymer concrete.